Prevalence and Antimicrobial Resistance Patterns of Multidrug-Resistant Bacterial Pathogens Isolated from Cancer Patients - Dumasiya, Prashant; Chodvadiya, Kalpesh (International Journal of Medical Research, 2016)
Background: Antimicrobial resistance has emerged as a major global health concern, particularly among immunocompromised populations such as cancer patients. Frequent hospitalization, invasive procedures, prolonged antibiotic exposure, and immunosuppressive therapies predispose cancer patients to infections caused by multidrug-resistant (MDR) organisms. These infections are associated with increased morbidity, mortality, and limited therapeutic options, highlighting the need for continuous surveillance of antimicrobial resistance patterns in oncology settings. Objectives: To isolate and identify Gram-positive and Gram-negative bacterial pathogens from clinical samples obtained from cancer patients and to determine their antimicrobial susceptibility patterns with special emphasis on multidrug-resistant organisms. Methods: A prospective observational study was conducted from January to March 2014. A total of 51 clinical samples, including pus, urine, blood, body fluids, wound swabs, sputum, tracheal secretions, stool, and central line tips, were processed using standard microbiological techniques. Bacterial identification was performed based on culture characteristics, Gram staining, and biochemical tests. Antimicrobial susceptibility testing was carried out using the modified Kirby-Bauer disc diffusion method according to CLSI guidelines. Multidrug resistance was defined as resistance to three or more classes of antibiotics. Results: Out of 51 samples, 27 (52.9%) yielded bacterial growth. Gram-negative organisms slightly predominated (51.9%). Escherichia coli (29.6%) was the most frequently isolated pathogen, followed by Staphylococcus aureus (25.9%) and Streptococci spp. (22.2%). Overall, 55.6% of isolates were multidrug resistant. The highest MDR rate was observed among E. coli (87.5%) and Pseudomonas aeruginosa (60.0%). Most isolates remained susceptible to carbapenems, colistin, linezolid, and rifampicin. Conclusion: The study demonstrates a high prevalence of multidrug-resistant bacterial pathogens among cancer patients, emphasizing the urgent need for rational antibiotic use, continuous resistance surveillance, and effective antimicrobial stewardship programs in oncology care settings.